Thiyl Radical-Mediated 'Click' Strategies for Site-Selective Peptide and Protein Modification - Rabadán González, Inés (Trinity College Dublin. School of Chemistry. Discipline of Chemistry, 2026)
Thiol-ene 'click' chemistry is a radical-chain-mediated reaction between a thiol and alkene that furnishes a robust, covalent thioether linkage. This reaction is considered a 'click' process due to its numerous beneficial attributes including chemoselectivity, rapid reaction times and tolerance to atmosphere conditions. Over the years, thiol-ene chemistry has been applied across diverse areas including chemical biology, polymer chemistry, materials science and for the synthesis of therapeutic agents. This thesis explores the development of thiol-ene mediated 'click' reactions for peptide and protein modification, with potential applications in peptide bioconjugation methodologies relevant to drug discovery and chemical biology. Chapter 2 presents a 'green' methodology for peptide bioconjugation. For the first time, peptide ligation was carried out under continuous-flow conditions using deep eutectic, bio-based solvents and aqueous conditions. The scope of this methodology was further expanded to the glycosylation of bioactive peptides demonstrating its scalable and sustainable advantages for the pharmaceutical industry.Chapter 3 describes the use of UV-initiated thiol-yne 'click' reaction for peptide disulfide rebridging. The use of NaBH4 as an emerging peptide disulfide reducing agent is investigated, since its use had previously been restricted to protein modifications. The strategy was extended to include a range of biomolecules and applied to an analogue of the naturally occurring hormone Somatostatin, with potential cellular bioimaging applications. Chapter 4 outlines the application of naphthalimides as a novel type of organic photocatalyst for thiol-ene-mediated photoredox catalysis. Their aggregation-induced emission properties enabled the study of this methodology in both organic and aqueous media. Several examples of successful ligation reactions employing the novel photocatalysts are presented. Chapter 5 focuses on the development of a covalent, site-selective thiol-ene-mediated mRNA display platform. This system consists of the incorporation of thiol-ene 'click' chemistry onto a standard mRNA display for more efficient discovery of peptide-based protein-protein interaction inhibitors. The efficacy of the thiol-ene mediated process is demonstrated on a model system, highlighting potential applications for library screening methods utilising this approach.
APPROVED
Keywords: Peptide bioconjugation; Click chemistry; Drug development; Covalent linker; Thiol-ene